Understanding Research Paradigms: A Scientific Guide - Yong, Wooi Keong *; Maizaitulaidawati, Md. Husin; Kamarudin, Suzilawati (CIBG, 2021)
Knowledge of research paradigms is crucial as they guide scientific research and discoveries through their assumptions and principles. Besides, different disciplines utilize different research approaches. There are four different research paradigms available - positivism, realism, critical theory, and interpretivism. Knowledge of the various research paradigms will reduce research method bias and allow for better research instruments. This paper aims to highlight to budding researchers the research paradigms available and their employment in scientific research.